(untitled) (Czech Journal of International Relations, 1967)
Purpose in power is the second part of the selected speech of the British prime minister. It follows on from the collection Purpose in Politics, which was reviewed in International Relations c. 4/66. While the first volume covers the period when the Labor Party was in opposition, the second volume formulates Wilson’s views on important domestic and foreign political issues from the position of prime minister and party leader in the first year of the Labor government (October 1964 — November 1965). Wilson’s speech shows the maximum application of a tactical approach. The extreme prudence of the right-wing government period was forced by the narrow majority in the parliament and the necessity to achieve unity in the party and to achieve, above all, a common approach with the left. Nevertheless, this analogy already indicated the course the new government intends to take, especially in its economic and foreign policy.